The Role of the Grab Application in Increasing Sales of Culinary SME Products from Shari'ah Marketing Perspective in Wonosobo Subdistrict - Salisa, Alaya Rizka; Sari, Putri Avinda; Astuti, Retno Puji; Khabib, Ainun (UM Purwokerto Press, 2025)
The development of technology and information plays an important role in economic growth. Today, the demand for technology and information in the culinary business is very high. The presence of GrabFood, a food delivery E-Commerce platform created by the Grab app, helps small and medium-sized enterprises (SMEs) in the culinary industry to market and grow their businesses. The purpose of this research is to understand the role of the Grab app in increasing the sales of culinary SME products in the Wonosobo subdistrict, as well as how culinary SME owners can operate and utilize digital applications to develop their businesses in accordance with Sharia principles.This research is a descriptive qualitative study, using observation and interview methods with SMEs that use GrabFood services in the Wonosobo subdistrict. The data sources used are primary and secondary data. Primary data sources are obtained directly from SMEs using GrabFood services, while secondary data sources are derived from books, journals, and articles relevant to the research theme. The results of this research show that the presence of GrabFood significantly helps culinary SMEs in marketing and increasing sales by enhancing distribution channels, information flow, communication, and the quality of human resources among culinary SMEs. From a Sharia marketing perspective, the use of digital marketing through the GrabFood service app by SMEs in Wonosobo subdistrict is in line with Sharia principles.